Achaemenid Understanding of Law and Justice in Darius I's Tomb Inscriptions: Are There Any Connections with Hebrew Bible Pentateuchal Conceptions?. Issue 1 (2nd January 2019) - Jonker, Louis C.
ABSTRACT: Sections of the so-called Fürstenspiegel (DNb), an inscription on the rock face of Darius I's tomb at Naqš i-Ruštam, are seen by scholars as a clear expression of royal Achaemenid legal and ethical understanding. An area which is still under-investigated in biblical scholarship is whether this imperial understanding, which undoubtedly was well-disseminated in other parts of the empire, also had an influence on the formulation of legal and ethical traditions in the Hebrew Bible, particularly in the Pentateuch. This paper will be an attempt to establish first steps for theorizing this connection, mainly with reference to the so-called Holiness Legislation.